Pleurotus ostreatus manganese‐dependent peroxidase silencing impairs decolourization of Orange II - Salame, Tomer M. (Blackwell Publishing Ltd, 2010)
Decolourization of azo dyes by Pleurotus ostreatus, a white‐rot fungus capable of lignin depolymerization and mineralization, is related to the ligninolytic activity of enzymes produced by this fungus. The capacity of P. ostreatus to decolourize the azo dye Orange II (OII) was dependent and positively co‐linear to Mn(2+) concentration in the medium, and thus attributed to Mn(2+)‐dependent peroxidase (MnP) activity. Based on the ongoing P. ostreatus genome deciphering project we identified at least nine genes encoding for MnP gene family members (mnp1–9), of which only four (mnp1–4) were previously known. Relative real‐time PCR quantification analysis confirmed that all the nine genes are transcribed, and that Mn(2+) amendment results in a drastic increase in the transcript levels of the predominantly expressed MnP genes (mnp3 and mnp9), while decreasing versatile peroxidase gene transcription (mnp4). A reverse genetics strategy based on silencing the P. ostreatus mnp3 gene by RNAi was implemented. Knock‐down of mnp3 resulted in the reduction of fungal OII decolourization capacity, which was co‐linear with marked silencing of the Mn(2+)‐dependent peroxidase genes mnp3 and mnp9. This is the first direct genetic proof of an association between MnP gene expression levels and azo dye decolourization capacity in P. ostreatus, which may have significant implication on understanding the mechanisms governing lignin biodegradation. Moreover, this study has proven the applicability of RNAi as a tool for gene function studies in Pleurotus research.